Meta-Analysis the Effects of Obesity and Type 2 Diabetes Mellitus on Covid-19 Mortality - Oktaviana Kurniawati; Hanung Prasetya; Bhisma Murti (Journal of Epidemiology and Public Health, 2021)
Background: COVID-19 is a disease caused by a new coronavirus called SARS-CoV-2. In more severe cases, COVID-19 can cause death. The most severe COVID-19 patient mortality is associated with underlying health conditions. The most common associated comorbidities are pulmonary disease, diabetes, obesity, and old age. However, the effects of obesity and T2DM disease on the 2019 coronavirus disease (COVID-19) pandemic are controversial. This study aims to analyze the magnitude of the influence of obesity and T2DM on COVID-19 mortality.Subjects and Method: This study uses a systematic review and meta-analysis research design. The time of the selected test results is between January 2020 to January 2021. The search for articles is carried out for 1 month. Research data was searched from databases: PubMed, Google Scholar, JAMA, Willey, and Science Direct. Using search keywords: (Type 2 diabetes mellitus OR diabetic) AND (mortality OR death) AND (COVID-19 /OR Coronavirus OR SARS-CoV-2) AND ("adjusted odds ratio" OR "aOR"), (obesity OR obese) AND (mortality OR death) AND (COVID-19 OR Coronavirus OR SARS-CoV-2) AND ("adjusted odds ratio" OR "aOR"). The inclusion criteria in this study were full-text articles in English, observational study designs were collected using PRISMA, and analyzed using the Review Manager application (RevMan 5.3).Results: A total of 15 articles were reviewed in this study. A meta-analysis of 10 cohort studies showed that people with COVID19 who had comorbid obesity were 1.50 times more likely to die from COVID-19 compared to those without obesity (aOR = 1.50; 95% CI = 1.17 to 1.93; p = 0.001). A meta-analysis of 6 cohort studies showed people with COVID-1919 who had comorbid T2DM 1.93 times to die from COVID-19 compared with those without T2DM (aOR = 1.93; 95% CI = 1.28 to 2.90; p = 0.002).Conclusion: Obesity and T2DM are predictors of COVID19 mortality.